The Importance of Imaging Techniques in Child Abuse - Beyaztaş, Fatma Yücel; Çelik, Muharrem; Bütün, Celal (The Bulletin of Legal Medicine, 2011)
Child abuse and neglect that caused serious injuries and even deaths, being a major public health problem, present medical, legal, and social aspects. Due to difficulties in diagnosing child abuse because of various narrations of the abusive event(s), controversial testimonies, and consultations to different health care centers each time, maintenance of high degree of suspicion has been advocated. In suspected cases of child abuse, and neglect, as emphasized in our case report, use of proper imaging modalities is crucial in order to recognize, and document the signs of abusive act. X-rays of all skeleton to evaluate bony structures, and computerized tomography (CT), magnetic resonance imaging (MRI), and ultrasound to detect visceral organ injuries should be preferred. Nowadays, imaging techniques of nuclear medicine have been introduced for the diagnosis of child abuse. In cases with child abuse accurate diagnosis should be established using objective medical evidence. Failure in diagnosis of child abuse causes the child to reside in the environment of abusive acts which consequently leads to more serious health problems or even death of the child. Misdiagnosis of child abuse will lead to unnecessary and unfair accusation of an innocent individual. In both conditions, legal, and ethical obligations, and responsibilities of the physicians will be interrogated. Establishment of accurate diagnosis using objective evidence in cases with child abuse is important with respect to proper treatment, and from the perspectives of ethical, and legal obligations. In conclusion, every possible medical opportunity should be used in order to diagnose child abuse, and clarify the judicial case. Guidelines and algorithms are available within the frame of good medical practice. The important benefits provided by imaging techniques as documentation, legal protection, and if deemed necessary, réévaluation of relevant information, and findings in cases with child abuse should not be forgotten. Key words: Child abuse, radiology, imaging techniques, virtopsy, forensic medicine.